Florida H2OSAV Insights: Home Water Use in Orange County - Nick Taylor; Kaitlin Olander Robb Price; Bradley Spatz; Parker Johnson; Pierce Jones (EDIS, 2021)
This fact sheet provides current, basic information about residential water use in Orange County. Written by Nick Taylor, Kaitlin Olander Robb Price, Bradley Spatz, Parker Johnson, and Pierce Jones, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2021.